2007
DOI: 10.3122/jabfm.2007.02.060045
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Dysphagia in Primary Care Patients: A HamesNet Research Network Study

Abstract: Purpose: A number of disorders cause dysphagia, which is the perception of an obstruction during swallowing. The purpose of this study was to determine the prevalence of dysphagia in primary care patients.Methods: Adults 18 years old and older were the subjects of an anonymous survey that was collected in the clinic waiting room before patients were seen by a physician. Twelve family medicine offices in HamesNet, a research network in Georgia, participated.Results: Of the 947 study participants, 214 (22.6%) re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
111
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 152 publications
(117 citation statements)
references
References 19 publications
4
111
0
2
Order By: Relevance
“…However, the reported prevalence rates vary, mainly due to the exact definition of dysphagia (4) and the used diagnostic instrument (5). It is estimated to occur in up to 52.7% of the elderly (2), 44-53.6% of patients with stroke (6, 7), up to 32% of patients with Parkinson's disease (8), and 48.4% of patients with head and neck cancer (9).…”
Section: Development Of the Brief Bedside Dysphagia Screening Test -Rmentioning
confidence: 99%
“…However, the reported prevalence rates vary, mainly due to the exact definition of dysphagia (4) and the used diagnostic instrument (5). It is estimated to occur in up to 52.7% of the elderly (2), 44-53.6% of patients with stroke (6, 7), up to 32% of patients with Parkinson's disease (8), and 48.4% of patients with head and neck cancer (9).…”
Section: Development Of the Brief Bedside Dysphagia Screening Test -Rmentioning
confidence: 99%
“…In a primary care practice research network, the prevalence of dysphagia was 23%. 3 In another primary care series, the prevalence of hoarseness was 11%. The association between gastroesophageal reflux disease (GERD) and laryngopharyngeal reflux (LPR) is well established, and extra-esophageal symptoms, eg, hoarseness and globus sensation, improve with acid suppression.…”
mentioning
confidence: 99%
“…It has been reported that dysphagia affects approximately 20% of the adult primary care population in the USA (Wilkins et al, 2007). Approximately 15% to 30% of hospital patients have swallowing difficulties or aspirate oral contents (Cichero et al, 2009, Altman, 2011.…”
Section: Dysphagiamentioning
confidence: 99%